Centro de excelencia en competitividad y emprendimiento: núcleo de desarrollo logístico provincia de Guaneta, San Gil Santander (2017)
The purpose of the urban and architectural proposal described in this document is to create a physical space that, based on academic training, fosters the economic development of the territory comprising the municipality of San Gil, in Santander, through The use of entrepreneurship and marketing strategies in line with contemporary globalization standards. To this end, it is established that, based on higher education and training, human capital will be trained to develop small and medium-sized enterprises that generate new employment practices, opening the gap in dynamic and alternative work environments to traditional ones. It proposes an urban equipment strategically implanted near the transport terminal to achieve the closest proximity to the national and international connectivity symbol alluding to the concept of globalization, in addition to its architectural characteristics of the building that will reflect the contemporaneity of the project in its entirety, from the Physical to functional.